Peningkatan Pengetahuan Orang Tua tentang Kekerasan Anak melalui Edukasi Berbasis Tree of Life - Venus Quartiana, Rivalda; Wijayanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2024)
Child, violence, parents Children are very easy to become victims of violence, because they are considered to be weak or unable to protect themselves. as individuals who are weak or unable to protect themselves. Based on the KPAI report in 2020, there were 3,087 cases of violence against children, with the perpetrators generally from the family or caregivers. family or caregivers. To prevent violence against children, prevention efforts prevention efforts must start from the family environment, especially parents, because parents have an important role in protecting children and parents have an important role in protecting children and preparing them to face a better, free to face a better life, free from violence. The purpose of this study was to increase parents’ knowledge about preventing violence against children through Tree of Life-based education.. against children using the Tree of Life method. This research method This research method uses quantitative research with Pre Test Post Test Design. The sampling technique is total sampling. Data analyzed using nonparametric statistical tests with the Wilcoxon test. Wilcoxon test. The results of the analysis showed a p-value of 0.001 which was smaller than 0.05, thus showing the test results nonparametric statistics with the Wilcoxon test prove there is a significant effect of education using the Tree method. significant effect of education using the Tree of Life method on increasing the knowledge of parents regarding the prevention of violence against children, at Sawahan Islamic Bakti Kindergarten.